Clinical Assessment of the use of Sublimated Mare's Milk in Complex Therapy of Mild and Moderate Psoriasis - Bakytgul Yermekbayeva (Journal of Global Pharma Technology, 2020)
The article discusses the therapeutic effect of mare's milk in complex treatment in patients with psoriasis. Research objective: Clinical assessment of the use of sublimated mare's milk in complex therapy of mild and moderate psoriasis. Materials and methods: 20 patients in main group with mild and moderate psoriasis took part in the study - control, who during 12 weeks of standard therapy took sublimated mare’s milk and 20 comparison group patients on standard therapy. In the study participants in main group, the severity index of psoriasis course and spread (PASI) was calculated at 0 and 12 weeks.Results: A statistically significant decrease in the PASI index was found: after 6 weeks by 68%, with treatment within 12 weeks - by 88% (p = 0.0003) in the main group compared with the comparison group. Conclusions: in patients with psoriasis, it is necessary to include sublimated mare's milk in the complex treatment to increase the effectiveness of therapy and lengthen the period of remission. Keywords: Psoriasis, PASI index, Sublimated mare's milk.